Optimisation of hydrolysis conditions for ethanol production from sorghum starch - Nadir, Najiah; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Mohd Yunus, Rosli (The Institution of Engineers, 2010)
The conversion of starch to sugar can be achieved by hydrolysis process. The two-step enzymatic hydrolysis of sweet sorghum was performed by commercially available α-amylase and glucoamylase. An optimisation study was carried out to optimise the factors of the hydrolysis process, namely, amount of substrate, liquefaction and saccharification temperature, liquefaction and saccharification time, and amount of α-amylase and glucoamylase enzymes. The screening of significant hydrolysis factors were done by using the two-level factorial design (TLFD) under the factorial design (FD). The results indicated that the liquefaction and saccharification temperature, and amount of glucoamylase enzyme were found to be the major factors for further optimisation. The major factors for hydrolysis were optimised by the central composite design (CCD) under the response surface method (RSM). The analysis of variance(ANOVA) result showed that glucoamylase enzyme (p < 0.0021) and saccharification temperature (p < 0.0181) were significant factors for hydrolysis of sorghum starch. Also, the statistical analysis showed that the optimum dextrose equivalent (69.07% (g/g)) were obtained at 90°C of liquefaction temperature, 47°C of saccharification temperature, and 0.24% (v/w) of glucoamylase enzyme.